Sequência didática para o ensino de astronomia nas aulas de geografia nos sextos anos na rede municipal de ensino de Santa Maria - RS - Kegler, Lucas Luiz (2024)
The main objective of this work was to develop a didactic sequence on knowledge of basic Astronomy, fundamental to Geography classes in the sixth year of Elementary education for the municipal network of Santa Maria, RS. Which mainly focused on the general characteristics of the Solar System, with the specific objectives being: to organize a textbook with a proposed didactic sequence for the sixth year; integrate the school with part of the educational equipment of the Cultural Route of the Federal University of Santa Maria (UFSM). The prerogative of being more experiential and practical work was maintained, for this reason it was based on socializing teaching-learning procedures, such as group work, according to HAYDT (2006). The action was developed during Geography classes in 2022 and It was organized in the form of a didactic sequence throughout the third quarter of that year in a municipal school in Santa Maria. The project was developed both at the school and in its surroundings in the neighborhood and beyond its walls, even reaching the Federal University of Santa Maria (UFSM). The activities of the didactic sequence consisted of: a Directed Review on the film The Martian (2015), the construction of models about the Solar System and a Tour Class (fieldwork) to the Cultural Route of the Federal University of Santa Maria with directional focus to the Planetarium, thus, each activity and its underlying tasks are one of the respective stages of the didactic sequence (DS). Therefore, the elaboration of the didactic sequence was completed and proved to be effective in the classroom and beyond, as it allowed expanding the teaching space beyond the school walls, connecting it to the University, through activities in the students' geographic space and expanding their citizenship education experience based on the search for scientific knowledge.